The Future of United States, China, and Taiwan Relations - Lin, C.; Lin, C.; Roy, D.; Roy, D. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Relations across the Taiwan Strait were unstable for decades before May 2008. Several acknowledged "crises" raised the possibility of war between China and the US and/or Taiwan and at times political disputes wracked the US-Taiwan relationship. Nevertheless, the Taiwan Relations Act (TRA) of 1979 helped maintain peace by deterring coercive actions by China against the island.